Characteristics of Carbapenem-Resistant Gram-Negative Bacilli in Patients with Ventilator-Associated Pneumonia - Amira Mohamed (MDPI AG, 2021)
Carbapenem-resistant Gram-negative bacilli (CR-GNB) has become a global threat. In hospital settings, the association of CR-GNB with ventilator-associated pneumonia (VAP) is a critical public health concern owing to their high resistance rate to most antibiotics. The present study aims to identify the frequency of carbapenem-resistance and to determine the rate of multidrug resistance (MDR), extensive drug resistance (XDR) and pan-drug resistance (PDR) among CR-GNB infections in VAP. Antimicrobial susceptibility testing was carried out using the disk diffusion method and the detection of carbapenemases was screened using the imipenem-E test and the modified carbapenem-inactivation method (mCIM). The isolates were verified by polymerase chain reaction (PCR) for the presence of blaNDM, blaSPM, blaVIM, blaIMP and blaGIM genes. 89.5%, 14%, 17.5%, 10.5%, 3.5% of isolates exhibited the presence of blaNDM, blaVIM, blaSPM, blaIMP and blaGIM, respectively. 76%, 17% and 7% of isolates were PDR, XDR, and MDR, respectively. Carbapenem-resistance genes were identified in a significant percentage and blaNDM was the most predominant gene. All isolates were highly resistant to most antibiotics. This health concern has proven to be a big challenge in developing countries such as Egypt, as it is associated with high morbidity, high mortality, and raised healthcare costs.